Design and fabrication of low-cost renewable carbon electrode materials and their thermo-kinetics for sustainable energy storage applications. (December 2022) - Semeniuk, M.; Ng, K.L.; Wang, Y.; Tjong, J.; Oksman, K.; Lu, Z.-H.; Azimi, G.; Sain, M.
Abstract: Low-cost, abundant biomass is a promising raw material for future applications in energy storage when processed into renewable graphitic carbon. To date, there have been few studies performed on the kinetics of thermal decomposition of renewable carbon and its use in energy storage devices. Novel renewable graphitic carbon from Acer saccharum, sugar maple (SM) heartwood, and Arachis hypogaea, peanut outer shell (PS), are used as anodes in lithium-ion coin cell batteries, with steady specific capacities of 180 mAh/g and 220 mAh/g, respectively, and both retain 100% columbic efficiency for over 350 cycles. Cyclic voltammetry reveals the different charge storage kinetic mechanisms of the two. The voltammogram of SM contains an oxidation peak indicating Li ion intercalation suitable for battery application, while PS lacks a peak; thus, showing potential for function as a supercapacitor. A kinetic study is undertaken on six carbon sources to improve the understanding of the thermal degradation process leading to renewable graphitic carbon. Consistent results are shown across the various model-free methods, indicating that they can accurately describe the devolatilization process. The renewable graphitic carbons morphological features were studied by SEM, XRD, Raman and nitrogen adsorption isotherms. As SM and PS compare favorably to the electrodes they replace, renewable graphitic carbon has the potential for use in a wide variety of novel applications, such as organic thin film transistors, fuel cells, organic batteries, supercapacitors, and other bioelectronics. Graphical abstract: Image 1 Highlights: Evaluated renewable graphitic carbon as an anode in lithium-ion coin cell battery Cyclic voltammetry determined charge storage kinetics mechanism for electrodes Peanut shell electrode maintained a consistent 220 mAh/g specific capacity Kinetic parameters were studied to better understand thermal degradation process Several model-free methods were used to determine the E a and α